Learning style preferences of preclinical medical students in a Malaysian university - Muralidhara, D.V.; Mohd Nasir, Mat Nor; Nordin, Simbak (2013)
Background: Academic demands of medical students are quite high. They require several skills involving sensory components such as visual, auditory, reading-writing and kinesthetic modes. The academic performance naturally differs in students and depends on their study habits including the learning style. It is believed that self- confidence is the first requisite to great achievements. Objective: We undertook this study to establish our hypothesis based on the assumption that students’ self-confidence and academic performance are directly related and the differences in learning style of each student could influence the academic performance. Method: To explore the pattern of preferred learning styles of 82 students, we administered the VARK questionnaire to the participants. To assess self-esteem, Rosenberg self-esteem questionnaire was used and the academic performance was based on the overall results of the formative assessments. Results: Among the respondents, 84% preferred multimodal style of learning. Out of that, dual, trimodal and quadrimodal styles were preferred by 8.5%, 2.4% and 73.2% respectively. The remaining 16% of the students preferred single mode. Female students had more diverse learning style preferences with several VARK combinations. A large proportion of our students were in the average group in terms of self- confidence and academic performance. Conclusion: Most students in this study preferred multimodal inputs in their learning process. Our study did not reveal any major gender differences in preferred learning styles. The results of self esteem, learning style preference and academic performance did not have any bearing on each other